Legal Response to Lone-Wolf Terrorism: A Global Review of Emerging Trends in Criminal Law - Lombu, Hadirat Syukur; Shodiq, Md.; Suasoongnern, Sineenart (Journal Evidence Of Law, 2025)
Lone-wolf terrorism poses a major challenge to modern criminal justice systems due to its decentralized, unpredictable, and often ideologically motivated nature. Unlike organized terrorist networks, lone actors tend to undergo radicalization independently and lack formal logistical support, rendering conventional law enforcement strategies less effective. This study uses a legal-normative method and a comparative law approach to examine the responses of four countries—the United States, the United Kingdom, France, and Indonesia—to this threat through their national criminal law frameworks. The results reveal significant differences in legal definitions, preventive measures, and standards of proof, reflecting the tension between national security needs and the protection of human rights. Common law countries are more likely to adopt proactive measures such as pre-crime intervention and movement restrictions, while civil law countries tend to be cautious in upholding the principle of legality and procedural safeguards. This article proposes universal legal principles that emphasize proportionality, legal certainty, and respect for human rights in responding to individual terrorism. The main contribution of this research lies in the development of a normative framework that can be used to harmonize national and international criminal law responses to the threat of individual terrorism.